Parameter-based modeling of nanoscale material thermal noise in gallium nitride high-electron-mobility transistors. (12th January 2021) - Madhulika,; Malik, Amit; Kamboj, Priyanka; Awasthi, Shivansh; Thakur, Priyanka; Jain, Neelu; Mishra, Meena; Kumar, Sanjeev; Rawal, Dipendra S; Singh, Arun K
Abstract: In this paper, we present an improved analytical model for predicting thermal noise in high-electron-mobility transistors (HEMTs) that considers the material's intrinsic properties at the nanoscale, specifically, its permittivity and melting point. The developed model is validated by comparing the results obtained from the computer simulation with experimental data for different device structures fabricated from an AlGaN/GaN-based two-dimensional electron gas. Furthermore, it is demonstrated that the nanoscale material's structural properties have to be considered to estimate the noise characteristics of the HEMT device accurately.